Boronic Acid Reagents for Transition‐Metal‐Mediated Cross‐Coupling with Proteins and Peptides. Issue 7 (1st April 2021) - Miller, Mary K.; Ball, Zachary T.
Abstract: Transition‐metal catalysis provides new approaches to selectivity and the activation of otherwise inert functional groups. Bioconjugation with protein and peptide substrates presents numerous challenges of functional group activation and selectivity, and transitional‐metal approaches provide important alternative solutions to these challenges. This article describes the development of boronic acid reagents for new selective approaches to modification of peptides and proteins, focusing primarily on catalytic C−X bond formation. Abstract :